Building 3D architectures for cardiomyocytes - Turgut, Aylin (2021)
Pharmaceutical companies currently rely on animal models for drug screening. This is a very expensive, time-consuming process and in some cases has been shown to be a poor predictor of human cardiac toxicity. Animal cells and tissue are not identical to their human counterparts. Therefore, it is not until human clinical trials at the later stages of drug screening that unexpected reactions to the drug are identified (Burridge et al., 2014). It would be greatly beneficial if this process could be shortened by identifying the risks of a drug earlier in the screening stages-chip based screening using mature human cardiomyocytes (CMs) is a route to achieve this. Substrates used to support CM growth have been identified including high-throughput chip-based screening strategies (Hook et al., 2013) (Celiz et al., 2014b) but so far stem cell derived CMs on these substrates do not adequately recapitulate the adult human CMs in terms of maturity (Denning et al., 2016). Many factors can affect how a cell matures from the soluble extracellular signals around it to the chemistry, topography, architecture/shape and mechanics of the substrate on which it is supported (Nikkhah et al., 2012). Mature cardiomyocytes have been successfully grown on 3 polymers synthesised by UV polymerisation-it has been confirmed that polymers like these can be successfully processed by 2-photon lithography. Photo initiator concentration has been optimised to create a complete structure. Glycerol propoxylate triacrylate and Tricyclodecane dimethanol diacrylate were shown to provide a wide operating window. Many relevant structures for CM growth were chosen and designed on AutoCAD to demonstrate the potential application of this material in CM culture. The 3D design freedom of the lithography approach will be used to explore the relationship between architecture and cell maturity. This will then enable a platform to be created using various architectures on a chip which will be utilised to assess cardiomyocyte maturity. This enables structure fabrication with more accuracy compared to previous methods due to the sub-micron scale of 2-photon lithography (Maruo et al., 1997). Greater resolution means improved results as cells interact on the sub-micron scale (~1µm) (Guck et al., 2010)Various architectures used for cardiomyocyte culture can show which ones are the most suitable to guide cardiomyocytes to a mature adult form.